ANALISIS BENTUK DAN PENGGUNAAN ONOMATOPE PADA ANIME HETALIA: WORLD STARS - Nurazizah, Erin; Fitriana, Ita; Yasmin Adellia Putri Fe (Indonesian language and literature education program Majapahit Islamic University, 2024)
Language serves as an agreed-upon symbol of sound used by humans for communication among groups. Each language has its unique characteristics, including onomatopes, which are words that describe sounds or conditions. Japanese is rich with onomatopes, categorized mainly into two types: gion-go (sounds from inanimate objects and nature) and gisei-go (sounds from living beings). Additionally, there exists gitai-go to describe silent states. In the context of the anime